Iron Deficiency Anemia and Its Impact on Oral Health-A Literature Review - Kabilan Velliyagounder; Krupa Chavan; Kenneth Markowitz (MDPI AG, 2024)
Oral disease interventions primarily focus on behavioral changes like dietary improvements and ensuring better oral hygiene. However, recognizing the influence of biological factors, including genetics and early-life nutrition, is crucial. Iron deficiency (ID) and its advanced form, iron deficiency anemia (IDA), affect nearly two billion people globally, especially children and pregnant women. We conducted a comprehensive search using Medline via EndNote and Web of Science, employing keywords related to iron deficiency anemia (IDA), and we identified 36 studies deemed relevant for inclusion in this literature review. IDA prevalence is notably high among pregnant women and young children. Both IDA and early-childhood caries (ECC) disproportionately affect impoverished populations, highlighting the socioeconomic dimension of this issue. IDA presents with various oral mucosal changes and is closely linked to candidiasis. Additionally, IDA can hinder tooth development and weaken the immune response. Multiple population surveys have revealed a significant association between ECC and IDA. While some studies have explored the IDA-periodontal disease link, the current evidence is relatively limited in its robustness. In conclusion, more comprehensive longitudinal studies are essential to deepen our understanding of the IDA-oral disease connection. Investigating the underlying biological mechanisms is critical to developing effective interventions, particularly for vulnerable populations affected by IDA.